HUBUNGAN TINGKAT SOSIAL EKONOMI TERHADAP TINGKAT PARTISIPASI POLITIK ETNIS KETURUNAN TIONGHOA DALAM PILWAKOT SEMARANG TAHUN 2010 - Heni Septi Wulandari; Nunik Retno H; Purwoko . (Journal of Politic and Government Studies, 2013)
AbstractBased on the diversity of culture, ethnicity, race and religion in Indonesia Thewriters interest to describe the mindset of the Chinese ethnic political participation. It isindicates highest legitimate authority by the people, measured from their involvement inthe democratic party (election). The results achieved in this study is to see the correlationof the socioeconomic level of the Chinese ethnic political participation in Semarangmayor election process (2010).The methodology research used by the author is quantitative descriptive research,in order to look at the relationship between variables. Data was collected throughquestionnaires method according to the number of samples. The results provide anoverview of data as a result of the overall conclusions regarding the overview of thesocio-economic level, to the level of political participation of Chinese ethnic.Results of this study shows that environmental factors and social status hasaffected their mindset to engage in political activities. The tendency of people choose toparticipate in a closed political, not following the political activities openly. They onlyparticipate by viewing and implement the system that has been determined by thepolitical elite. It is supported on the grounds that their income was categorized low, sopeople prefer the subject not work on political activity or state.Key words : Elections, Political Participation, Chinese Ethnicity, Social andEconomic